NEUROSCIENCE IN THE ELEMENTARY SCHOOL CURRICULUM: BUILDING THE CHARACTER AND SOUL OF PANCASILA IN LEBAK, BANTEN - Masilihah Zahroh Agustina; Wiwit Yuliesie; Lukman Nulhakim; Atin Fatimah (JURNAL NALAR PENDIDIKAN, 2025)
This study examines the integration of neuroscience into the school curriculum to enhance students' character development in accordance with Pancasila values. Using a mixed-method approach, the research combines qualitative and quantitative analyses through surveys, interviews, and classroom observations. Participants included 60 individuals, comprising fifth-grade elementary students, teachers, and the principal from a public elementary school in Lebak Regency, Banten, Indonesia. The intervention employed neuroscience-based learning strategies, including Project-Based Learning, Problem-Based Learning, and mindfulness activities. The findings suggest that implementing neuroscience principles enhances students' understanding of moral and social values, while also improving empathy, cooperation, and emotional awareness. The study concludes that integrating neuroscience into education supports both cognitive development and holistic character formation aligned with Pancasila values. It emphasizes collaboration among educators, neuroscientists, and policymakers in creating an inclusive, brain-friendly curriculum to support Indonesia's national education goals